2013
DOI: 10.1007/s00520-013-2002-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity preferences of early-stage lung cancer survivors

Abstract: Purpose Engagement in physical activity can provide important benefits for cancer patients and survivors, including those diagnosed with lung cancer. Despite this, many survivors do not engage in recommended levels of physical activity and little is known about the obstacles encountered by lung cancer survivors. The current study examines the physical activity preferences of early-stage lung cancer survivors. Method As part of a larger survey study, 175 non-small cell lung cancer survivors who were on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 40 publications
1
45
1
Order By: Relevance
“…In a recent study of 175 patients with nonsmall cell lung cancer who, on average, were 3.6 years postsurgery, Philip and colleagues observed that the clear majority desired advice regarding physical activity, with 80% identifying a preference for a face‐to‐face recommendation by a physician, and 92% stating that they preferred this interaction under the auspices of a cancer center . Although the generalizability of these findings may be limited, there is little debate that one of the most powerful influences over patients' behavior is the recommendation of the physician.…”
Section: Healthy Lifestylementioning
confidence: 99%
“…In a recent study of 175 patients with nonsmall cell lung cancer who, on average, were 3.6 years postsurgery, Philip and colleagues observed that the clear majority desired advice regarding physical activity, with 80% identifying a preference for a face‐to‐face recommendation by a physician, and 92% stating that they preferred this interaction under the auspices of a cancer center . Although the generalizability of these findings may be limited, there is little debate that one of the most powerful influences over patients' behavior is the recommendation of the physician.…”
Section: Healthy Lifestylementioning
confidence: 99%
“…Cancer survivors may therefore particularly seek guidance on appropriate physical activity (i.e. quantity, duration, physical activity type), and how to be physically active following diagnosis (Philip et al., ). However, a recent review of the availability of information about lifestyle for cancer survivors in England from statutory and charitable sector organisations and from cancer centres, found that most did not provide adequate information and advice about lifestyle for cancer survivors (Williams et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen (56%) studies measured PA using patient self‐reported questionnaires, surveys or diaries (Table ). The most commonly used questionnaire was The Godin Leisure Time Exercise Questionnaire (GLTEQ), or a modified version, being used in seven studies . Other questionnaires utilized include the Physical Activity Scale for the Elderly (PASE), Baecke Physical Activity Questionnaire, Rotterdam Symptom Checklist and Stage of Change Physical Activity Questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐six percent of included studies used patient‐reported measures. The most frequently used PROM was the GLTEQ, being reported in seven studies of five patient samples . Next commonly, the PASE was reported in two studies .…”
Section: Discussionmentioning
confidence: 99%